STRATEGI PEMASARAN TOKO PAKAIAN MUSLIM PASAR TRADISIONAL MENGHADAPI TOKO PAKAIAN MUSLIM MODERN - Sutrisno Sutrisno; Jamianto Jamianto; Budi Andreanto (Yos Soedarso Economic Journal (YEJ), 2021)
Indonesia is one of the countries that has entered the era of global competition, where there are no restrictions for each individual to develop a business, both small, medium and large. With the development of global competition that cannot be stopped, it results in small businesses being unable to compete with middle and upper class businesses in the business world.Competition between shops or kiosks in conventional markets and online shops cannot be avoided. The flood of online shops in cities cannot be stopped. The thing that can be done is to be ready to face it and to anticipate it so that the existence of a shop or kiosk in conventional markets is not eroded by the existence of an online shop.Keywords: Global Competition; Online Business.